Factors Influencing Forest Dependency on the Gola Rainforest Reserve in Sierra Leone - Samura, Philip (International Journal of Environmental Sciences, 2024)
Purpose: Forests are under intense human pressure due to a high level of dependency. Understanding socioeconomic and demographic incentives surrounding forest dependence is critical to mitigating the adverse impacts of forest degradation in Africa. Therefore, this study examines the factors promoting household forest dependence in Sierra Leone's Gola Rainforest Reserve through four research questions: (1) What is the contribution of forest income relative to total household income? (2) What are the key sources of relative forest income? (3) How do gender, age, and education influence forest dependency? (4) What factors drive dependence on forest resources? Methodology: The study's target population was rural households living near the Gola Rainforest Reserve in Gaura and Tunkia Chiefdoms in the Kenema district. The study used convenience sampling. A questionnaire and an interview guide were used for data collection. It drew from 101 survey responses analyzed using descriptive and inferential statistics, binary logistic regression on S.P.S.S., and then "”seven expert interviews and three focus group discussions explored with thematic analysis on Google Docs. The study used tables and figures for data presentation. Findings: The study's results showed four key findings. First, forest income accounts for 46% of monthly household income in the sampled community. Second, the top five sources of forest income are cocoa (74%), moringa tea (9%), timber wood (4%), forest spices (4%), and forest fruit and vegetables (3%). Third, age, education, and gender influence forest dependence. Fourth, livelihood and direct consumption are the key factors driving dependence on forest resources. Therefore, the study recommended that decision-makers and conservationists consider socioeconomic factors like gender, age, education, and livelihood when designing forest management projects, strategies, or policies. Unique Contribution to Theory, Practice, and Policy: The study's outcome contributes to the growing literature on forest dependency. It provides key insights into the significant contribution of forest resources to household income. Analyzing the influence of socio-demographic factors, like gender, age, and education, on forest resources enhances the understanding of resource-use patterns. This study allows forest conservationists, government decision-makers, and academics to develop projects, policies, and strategies from an informed perspective, considering socio-economic realities, to promote sustainable forest management practices in Sierra Leone and other developing countries to mitigate deforestation.